2012
DOI: 10.1038/emboj.2012.246
|View full text |Cite
|
Sign up to set email alerts
|

Endoglin mediates fibronectin/α5β1 integrin and TGF-β pathway crosstalk in endothelial cells

Abstract: Both the transforming growth factor b (TGF-b) and integrin signalling pathways have well-established roles in angiogenesis. However, how these pathways integrate to regulate angiogenesis is unknown. Here, we show that the extracellular matrix component, fibronectin, and its cellular receptor, a5b1 integrin, specifically increase TGF-b1-and BMP-9-induced Smad1/5/8 phosphorylation via the TGF-b superfamily receptors endoglin and activin-like kinase-1 (ALK1). Fibronectin and a5b1 integrin increase Smad1/5/8 signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
78
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(84 citation statements)
references
References 58 publications
5
78
0
1
Order By: Relevance
“…The enhanced endoglin expression by TPSC may contribute to increased responsiveness to profibrotic stimuli by TGF-β and thus promote the excessive fibrotic process in the pancreatic tumor stroma, as previously shown for murine hepatic stellate cells [20]. Furthermore, endoglin contains an RGD-sequence that enables cell adhesion via interaction with integrin receptors and ECM components such as fibronectin [21]. Endothelin-1 has previously been reported to be expressed by primary rat PSC and to stimulate their contraction and migration [22].…”
Section: Discussionmentioning
confidence: 82%
“…The enhanced endoglin expression by TPSC may contribute to increased responsiveness to profibrotic stimuli by TGF-β and thus promote the excessive fibrotic process in the pancreatic tumor stroma, as previously shown for murine hepatic stellate cells [20]. Furthermore, endoglin contains an RGD-sequence that enables cell adhesion via interaction with integrin receptors and ECM components such as fibronectin [21]. Endothelin-1 has previously been reported to be expressed by primary rat PSC and to stimulate their contraction and migration [22].…”
Section: Discussionmentioning
confidence: 82%
“…For example, TGF-β signaling inhibition decreases retinal perfusion and impairs endothelial barrier function in mice [206], while other authors have reported a TGF-β-mediated inhibition of proangiogenic molecules [207] or a proangiogenic effect of TGF-β blockade [208]. Moreover, Smad1/5/8-mediated blockade of EC migration [209], and the inhibition of tip cell differentiation -with a migratory phenotype-by BMP9 signaling through ALK1-Smad1/5/8 have been described [40]. We should take into account, as discussed above, that different TGF-β concentrations may exert opposite effects on ECs, further complicating the dissection of the precise effect of endoglin.…”
Section: Endoglin Regulation Of Focal Adhesions During Ec Migrationmentioning
confidence: 99%
“…Human endoglin displays the prototypic RGD motif involved in integrin-based interactions within its ZP juxtamembrane domain [84,85]. In addition, a physical and functional interplay between endoglin and β1 integrins has been reported [107,196,209,234]. More recently, endothelial endoglin has been identified as a ligand for leukocyte integrins [27].…”
Section: Endoglin Regulation Of Mural and Mononuclear Cell Recruitmentmentioning
confidence: 99%
See 1 more Smart Citation
“…53 However, it was reported that ALK1-endoglin complex is formed in vascular endothelial cells cultured on fibronectin matrix and mediates Smad1/5/8 signal in the absence of ALK5. 56 In the current experiment, HUVECs were cultured on fibronectin-rich (data not shown) fibroblast feeder later and thus might not require ALK5. The effect of promoting branching of the newly formed tube-like structure was more marked with SB431542 as compared with the samples supplemented with SIS3 in TGFβ1-plus culture.…”
Section: Tgfβ1mentioning
confidence: 99%